Spin transport and spin-caloric effects in (Cr,Zn) Te half-metallic nanostructures: Effect of spin disorder at elevated temperatures from first principles - Kovacik, Roman; Mavropoulos, Phivos; Blügel, Stefan (PHYSICAL REVIEW B, 2015)
An important contribution to the thermoelectric and spin-caloric transport properties in magnetic materials at elevated temperatures is the formation of a spin-disordered state due to local moment fluctuations. This effect has not been largely investigated so far. We focus on various magnetic nanostructures of CrTe in the form of thin layers or nanowires embedded in ZnTe matrix, motivated by the miniaturization of spintronics devices and by recent suggestions that magnetic nanostructures can lead to extraordinary thermoelectric effects due to quantum confinement. The electronic structure of the studied systems is calculated within the multiple scattering screened Korringa-Kohn-Rostoker Green function (KKR-GF) framework. The Monte Carlo method is used to simulate the magnetization in the temperature induced spin disorder. The transport properties are evaluated from the transmission probability obtained using the Baranger-Stone approach within the KKR-GF framework. We find qualitative and quantitative changes in the thermoelectric and spin-caloric coefficients when spin disorder is included in the calculation. Furthermore, we show that substitutional impurities in CrTe nanowires could considerably enhance the Seebeck coefficient and the thermoelectric figure of merit.